Extended Open-flow Technique for Reducing Handover Latency of PMIPv6 - Indumathi, L. K. (Theory and Applications of Engineering Research Vol. 7, 2024)
The IETF standardized PMIPv6, a network-based mobility management protocol. It is a protocol that supports several access technologies, including WLAN-based access designs, 3GPP, 3GPP2, and WiMAX, and builds a common and access technology independent of mobile core networks. The only network-based mobility management protocol that the IETF has standardized is Proxy Mobile IPv6. Unlike the Mobile IP technique, this job is carried out by the network, which is in charge of monitoring the host's motions and triggering the necessary mobility signaling on its behalf. To preserve the same IP address across multiple interfaces, the host must make adjustments akin to those for mobile IP in the event that mobility involves several network interfaces. This proposed technique adapts PMIPv6 to the Extended Open-Flow architecture, and this technique is referred to as the Extended Open-Flow Technique of PMIPv6 (EOFT-PMIPv6). This method isolates the versatility capacities from the PMIPv6 segments, for example, the Local Mobility Anchor (LMA) and Mobile Access Gateway (MAG), and recreates the parts to take points of interest of the Open-Flow design. The parts that contain the LMA work set the stream table of the switches situated in the way as the controller of Open-Flow, and as such, the area of the MN is kept up. The entrance switches with the MAG capacities tell the connection of a MN and introduce the portability related motioning of MAG. The fundamental commitments of this proposed strategy are twofold: 1) isolating the control and data planes and 2) reducing handover latency.